Analysis of the Effects from Adding Propeller Boss Cap Fins to Skewed Propeller Performance With CFD Methods - Irfan Syarief Arief; Achmad Baidowi; Anson Novendra Pradana (International Journal of Marine Engineering Innovation and Research, 2021)
Fuel accounts for the majority of the ship's operating costs. Increased propeller efficiency can help to reduce fuel usage. The higher the efficiency, the less energy is wasted. Ships with high propeller efficiency may be able to provide more thrust while using less fuel. Propeller Boss Cap Fin (PBCF) installation is one of the solutions for improving propeller efficiency that is ideal for a submarine. PBCF may lower the submarine's energy usage, allowing it to recharge its batteries less frequently. According to certain studies, PBCF can boost propeller efficiency by 7% while lowering noise levels by nearly 6 decibels (dB). The impact of PBCF phase lag variation on skewed propeller performance and flow will be the subject of this article. CFD simulation using phase lags of 0, 12.86, 25.72, and 38.58 will be used in the study. The simulation shows that PBCF can improve propeller efficiency while lowering propeller torque. Even though all phase lag modifications show a reduction in propeller thrust. On its hub vortex, they also reveal the existence of distraction.